Design for 3D printing / : scanning, creating, editing, remixing, and making in three dimensions - Bernier, Samuel N., ....-; Luyt, Bertier, ....-; Reinhard, Tatiana, ....- (San Francisco : Maker Media, 2015)
Not too long ago, operating a desktop 3d printer meant building your own, tweaking, tuning, and constantly upgrading. No more--3d printing has expanded into schools, libraries, homes, makerspaces, and hackerspaces. It's easy to get started with 3d printing, but it takes work to become a great 3d designer. Once you've graduated from downloading other peoples' model and doing simple rudimentary modeling of your own, you're going to want to try your hand at making something beautiful and enduring. Make: Design for 3D Printing gets you going with professional-level (and free!) design tools, and shows you how to model, scan, and perfect your designs. You'll learn amazing tips and tricks along the way, such as how to make 3D-printed moving models that print in place: take them off the printer, give them a wiggle, and they are ready to move!
Keywords: Three-dimensional printing -- HOWEST